Seksualno in umetnost sta eno - Mitrović, Slađana (Monitor ISH, 2009)
The creative opus of Pablo Picasso (1881-1973) has, with its intense outburst of sexual drive, excessive over-pouring of eroticism and intransigent dissolution into the explicitness of the body provided a deep shift within the traditional placing of sexuality into the classification of non-artistic practices. Afterwards the entire creative potence has been inherently sexualised, so profoundly interwoven with sexuality that no dividing line could ever be imposed between the two. The following article is aiming to think over the relation between sexuality and art in the series of graphics entitled Rafael and Fornarina, within a comprehensive project of graphic arts Suite 347 in the artist's last creative period. The series expresses an extraordinary stroke of co-positioning of Rafael and Fornarina's sexual intercourse in the very same moment with the act of painting.
Keywords: Picasso, Pablo, 1881-1973; seksualnost; visual arts; likovna umetnost; psihoanaliza